EFFECTS OF NATURAL LANDSCAPE FEATURES ON THE RURAL SETTLEMENTS: THE CASE STUDY OF BARTIN - Yılmaz, Bülent; Atik, Gonca (Bartın Üniversitesi, 2006)
Natural features of a land play an important role on lands development and organization. Unconscious andunplanned development of settlements which are arisen without taking into consideration of the natural featuresof the land harms the ecologic balance by hindering sustainability of natural resources. According to this,inadequate living conditions for human comfort have been arisen.In this study, factors that are related to natural landscape have been analyzed based on the interaction between 83rural settlement areas in the city of Bartin and 14 in the district of Arit. For this aim, natural structure features ofstudy area have been mapped using the GIS (Geographic Information Systems) tool, Arc View 3.2 software andacquired data has been compared with rural settlement areas. To sum up, the importance of natural landscapefeatures for the needs of settlements with the balance of their environs has been resulted.

Bir alanın sahip olduğu doğal özellikler, yerleşimlerin gelişimi ve şekillenmesinde büyük bir rol oynamaktadır.Doğal özellikler dikkate alınmadan ortaya çıkan yerleşimlerin bilinçsiz ve plansız gelişimi, ekolojik dengeyezarar vererek doğal kaynaklarının sürdürülebilirliğini engellenmektedir. Buna bağlı olarak da insan konforubakımından elverişsiz yaşam ortamları oluşmaktadır.Bu çalışmada, doğal peyzaja ilişkin faktörlerin Bartın merkez ilçeye bağlı 83, Arıt beldesine bağlı 14 kırsalyerleşim ile etkileşimi incelenmiştir. Bu amaç doğrultusunda, araştırma alanına ilişkin doğal yapı özellikleriCoğrafî Bilgi Sistemleri (CBS) yazılımlarından ArcView 3.2 programı kullanılarak haritalanmış ve elde edilenveriler kırsal yerleşim alanları ile çakıştırılmıştır. Sonuç olarak, doğal peyzaj özelliklerinin, yerleşimleringereksinimleri ile çevresi arasındaki dengenin sağlanabilmesi bakımından taşıdığı önem ortaya konulmuştur.
DOĞAL PEYZAJ ÖZELLİKLERİNİN KIRSAL YERLEŞİMLER ÜZERİNDEKİ ETKİLERİ: BARTIN ÖRNEĞİ